2009
DOI: 10.1242/jcs.050443
|View full text |Cite
|
Sign up to set email alerts
|

Direct recruitment of H+-ATPase from lysosomes for phagosomal acidification

Abstract: The nascent phagosome progressively establishes an acidic milieu by acquiring a proton pump, the vacuolar-type ATPase (V-ATPase). However, the origin of phagosomal V-ATPase remains poorly understood. We found that phagosomes were enriched with the V-ATPase a3 subunit, which also accumulated in late endosomes and lysosomes. We modified the mouse Tcirg1 locus encoding subunit a3, to express an a3-GFP fusion protein. Live-cell imaging and immunofluorescence microscopy revealed that nascent phagosomes received the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 51 publications
6
119
1
Order By: Relevance
“…Embryonic stem cell-mediated gene targeting was used to generate mice in which an a3 subunit-GFP fusion protein is expressed under the original promoter of the a3 subunit (a3-GFP mice) (13). Using bone tissue sections from these mice, we confirmed that tartrate-resistant acid phosphatase-positive (TRAPpositive) mature osteoclasts express GFP (Supplemental Figure 1C).…”
Section: Resultsmentioning
confidence: 74%
“…Embryonic stem cell-mediated gene targeting was used to generate mice in which an a3 subunit-GFP fusion protein is expressed under the original promoter of the a3 subunit (a3-GFP mice) (13). Using bone tissue sections from these mice, we confirmed that tartrate-resistant acid phosphatase-positive (TRAPpositive) mature osteoclasts express GFP (Supplemental Figure 1C).…”
Section: Resultsmentioning
confidence: 74%
“…Previous studies revealed that phagosomal acidification starts early during phagosome formation, before acquisition of lysosomal features such as LAMP-1 and cathepsins (8,53,54), which are recruited to phagosomes through distinct kinetics and mechanisms (7,35,55). Recently, it was shown that early recruitment of the a3 subunit of the v-ATPase to young phagosomes occurs via tubular structures extending from the perinuclear lysosomes along microtubules (56). This finding is consistent with previous studies showing that phagosomes acquire lysosomal features through a microtubuledependent mechanism (47,50).…”
Section: Discussionmentioning
confidence: 99%
“…An essential step during the degradation of autophagy substrates is the formation of autolysosomes upon fusion between the autophagosomes and the lysosomes and the activation of hydrolases upon acidification (Sun-Wada et al, 2009). Interestingly, LC3…”
Section: Introductionmentioning
confidence: 99%